(3x+2)+11=(22-x)+11

Simple and best practice solution for (3x+2)+11=(22-x)+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+2)+11=(22-x)+11 equation:


(3x+2)+11=(22-x)+11

We simplify the equation to the form, which is simple to understand
(3x+2)+11=(22-x)+11

Remove unnecessary parentheses
3x+2+11=(22-x)+11

Remove unnecessary parentheses
3x+2+11=22-x+11

We move all terms containing x to the left and all other terms to the right.
+3x+1x=+22+11-2-11

We simplify left and right side of the equation.
+4x=+20

We divide both sides of the equation by 4 to get x.
x=5

See similar equations:

| -3(-4-2n)=36 | | G=5/2-21 | | 5(.75)-2y=-9 | | 2.99=19.99+1.99 | | 180-148= | | -22=6y+2(y+5) | | -13x+12-11+15x=4(3x-7)-1 | | 4/7x=3/14 | | 2.99=1999+199 | | 1/2z+7=-3 | | 4x+3x-140=56 | | 7z+11-4-1+1=31 | | 2m-5/9 | | (3c-3)(4c+8)= | | 8w+6=-2(w-7) | | lx+3l=3x+6 | | 3(x+5)-2x=15 | | 6x-77+2x=43 | | -16/9=-8u | | 7x-2(1+3x)=2 | | 18+5w=3w-10 | | 5y-3/5=4/3 | | -(3v+4)=6v-3(3v+2) | | 77+4x=43 | | -2x(3x+4)+y=0 | | 0+1x=0.2(x+2) | | 3W-6+6W=-2+W | | -2/3t=6 | | 5x-x=12+6x | | 9w-2=-1w-22 | | -x-40+4x=26 | | 7v/6=-35 |

Equations solver categories